Amaranthus hypochondriacus L. as a Sustainable Source of Nutrients and Bioactive Compounds for Animal Feeding - Marianna Oteri; Fabio Gresta; Annalisa Costale; Vittorio Lo Presti; Giorgia Meineri; Biagina Chiofalo (MDPI AG, 2021)
With the aim to explore the use of A. hypochondriacus seeds for animal feeding, the agronomic traits, nutrients, and bioactive compounds of four accessions with different origin (India, Nebraska, Iowa, and Pennsylvania) grown in a Mediterranean environment were studied. Proximate composition was determined using the official methods of analyses, fatty acid profile by gas chromatography, total phenolic content (TPC) and the scavenging activity (DPPH• and ABTS•+) by colorimetric method. A one-way ANOVA model was performed to determine the differences between accessions. The four A. hypochondriacus accessions showed interesting seed yield results. No significant differences were observed for crude protein and crude fiber; the oil content showed the significant highest values in the seeds from Nebraska and Pennsylvania, but their nutritional characteristics were significantly different. The accession from Nebraska showed the highest oleic and linoleic acid levels, the highest values of polyunsaturated fatty acids, the best atherogenic and thrombogenic indices and hypocholesterolemic/hypercholesterolaemic ratio, and the highest TPC content. The accession from Pennsylvania showed the highest antioxidant activity and lowest peroxidation index. On the whole, A. hypochondriacus seeds can be used as pseudo-cereal to balance the animal diet and the accession should be chosen according to the different metabolic pathways of unsaturated fatty acids in ruminant and monogastric animals.